Using System Virtualization to Create Virtualized Networks - Berl, Andreas; Fischer, Andreas; de Meer, Hermann (Electronic Communications of the EASST, 2009)
The method of system virtualization is very popular for the use in data centers and desktop virtualization today. In this work, system virtualization is applied to core network elements (routers and links) in order to create a virtualized network. The selection of this virtualization method crucially determines the emerging network model. The network model consists of virtual networks, virtual routers, and virtual links that form overlays on top of the physical network. The properties, features, and limitations of this network model are analyzed and described in this paper. Additionally, a proof of concept implementation using currently available technology and infrastructure is presented. Finally the dynamic configurability of virtual resources in such a system virtualization based virtualized network is evaluated.